An explorative study towards the chemical synthesis of the immunoglobulin G1 Fc CH3 domain. (22nd October 2018) - Grassi, Luigi; Roschger, Cornelia; Stanojlović, Vesna; Cabrele, Chiara
Abstract : Monoclonal antibodies, fusion proteins including the immunoglobulin fragment c (Ig Fc) CH2‐CH3 domains, and engineered antibodies are prominent representatives of an important class of drugs and drug candidates, which are referred to as biotherapeutics or biopharmaceuticals. These recombinant proteins are highly heterogeneous due to their glycosylation pattern. In addition, enzyme‐independent reactions, like deamidation, dehydration, and oxidation of sensitive side chains, may contribute to their heterogeneity in a minor amount. To investigate the biological impact of a spontaneous chemical modification, especially if found to be recurrent in a biotherapeutic, it would be necessary to reproduce it in a homogeneous manner. Herein, we undertook an explorative study towards the chemical synthesis of the IgG1 Fc CH3 domain, which has been shown to undergo spontaneous changes like succinimide formation and methionine oxidation. We used Fmoc‐solid‐phase peptide synthesis (SPPS) and native chemical ligation (NCL) to test the accessibility of large fragments of the IgG1 Fc CH3 domain. In general, the incorporation of pseudoproline dipeptides improved the quality of the crude peptide precursors; however, sequences larger than 44 residues could not be achieved by standard stepwise elongation with Fmoc‐SPPS. In contrast, the application of NCL with cysteine residues, which were either native or introduced ad hoc, allowed the assembly of the C‐terminal IgG1 Fc CH3 sequence 371 to 450. The syntheses reported here show advantages and limitations of the chemical approaches chosen for the preparation of the synthetic IgG1 Fc CH3 domain and will guide future plans towards the synthesis of both the native and selectively modified full‐length domain. Abstract : Different fragments of the lgG1 Fc CH3 domain have been synthesized by Fmoc‐SPPS and evaluated for their suitability as precursors for native chemical ligation